Second annual report of the Hospital for Natural Healing : 1936-7 - Hospital for Natural Healing (London, England) (1937)
1937 1937 1930s 13 pages [photograph] Patient receiving "Heala" Ray treatment on Neck and Shoulder. [photograph] Patient receiving Osteopathic treatment. [photograph] A corner of the Dispensary. 292/842/2/237